2022
DOI: 10.1038/s41598-022-11079-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular survey and phylogenetic analysis of Babesia vogeli in dogs

Abstract: Canine babesiosis is a life-threatening haemoparasitic disease in dogs that is prevalent worldwide. In this study, the prevalence of Babesia vogeli (B. vogeli) was investigated in dogs from Egypt by using Polymerase Chain Reaction (PCR) assay, and associated risk factors were evaluated. In addition, phylogenetic position of B. vogeli Egyptian isolate was determined by sequencing. A total of 275 blood samples were taken from dogs located in four governorates belonging to the north of Egypt. Samples were examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In this study, B. vogeli was detected in 18 (5.34%) of 337 blood samples. The prevalence of the parasite was 2.1% in Malaysia [ 37 ], 4.8% in Brazil [ 38 ], 5.1% in Egypt [ 39 ], 5.1% in Iraq [ 40 ], 8.5% in Bosnia and Herzegovina [ 41 ], 9.3% in Iran [ 42 ], and 10.8% in Nigeria [ 43 ]. When the studies given above were evaluated, it was seen that the prevalence of B. vogeli was quite different.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, B. vogeli was detected in 18 (5.34%) of 337 blood samples. The prevalence of the parasite was 2.1% in Malaysia [ 37 ], 4.8% in Brazil [ 38 ], 5.1% in Egypt [ 39 ], 5.1% in Iraq [ 40 ], 8.5% in Bosnia and Herzegovina [ 41 ], 9.3% in Iran [ 42 ], and 10.8% in Nigeria [ 43 ]. When the studies given above were evaluated, it was seen that the prevalence of B. vogeli was quite different.…”
Section: Discussionmentioning
confidence: 99%
“…Although the authors of that study indicated other risk factors (e.g., male sex or various exotic dog breeds) [ 244 ], those parameters were not statistically insignificant ( p -values higher than 0.05), and therefore cannot be considered as risk factors for B. vogeli infection in Nigeria. A study from Egypt on the prevalence of B. vogeli infection in 275 dogs showed that the higher risk of infection in male dogs was not statistically significant [ 267 ]. The only significant risk factors for infection in dogs from Egypt were the soil type of the floor in dog shelters (OR = 6.1) in comparison to paved floors, and tick infestation (OR = 3.8) in comparison to a lack of tick infestation [ 267 ].…”
Section: Risk Factors For Large Babesia Infectionsmentioning
confidence: 99%
“…A study from Egypt on the prevalence of B. vogeli infection in 275 dogs showed that the higher risk of infection in male dogs was not statistically significant [ 267 ]. The only significant risk factors for infection in dogs from Egypt were the soil type of the floor in dog shelters (OR = 6.1) in comparison to paved floors, and tick infestation (OR = 3.8) in comparison to a lack of tick infestation [ 267 ]. However, a study from Brazil did not find an association between the type of the floor where dogs were kept and the frequency of infection with the parasite [ 241 ].…”
Section: Risk Factors For Large Babesia Infectionsmentioning
confidence: 99%
“…Later, with the development of DNA sequencing technology and other molecular based approaches, it was found that although the morphology of these infected dogs was similar, the genes they encode for were Babesiosis, also known as piroplasmosis, is a disease caused by Babesia protozoan parasites that use variety of ticks as natural vectors (Hildebrandt et al 2021;Krause 2019). The disease is mainly transmitted by ticks when they bite the host (Selim et al 2022). Babesia proliferates and destroys the infected erythrocytes of susceptible hosts(García-Quesada et al 2021).…”
Section: Introductionmentioning
confidence: 99%